2015
DOI: 10.1007/s12010-015-1508-3
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Polycyclic Aromatic Hydrocarbons (PAHs) by Laccase in Rhamnolipid Reversed Micellar System

Abstract: Rhamnolipid was applied to degrade anthracene and pyrene in reversed micelles. The parameters in degradation were optimized for the purpose of improving degradation rates. The proper amount of rhamnolipid (RL) used for degrading anthracene was 0.065 mM, while 0.075 mM for pyrene. However, reaction time for degrading both anthracene and pyrene was 48 h. The optimum water content, pH, laccase concentration, polycyclic aromatic hydrocarbon (PAH) initial concentration, and volume ratio of n-hexanol to isooctane fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 36 publications
(24 reference statements)
0
9
0
Order By: Relevance
“…The type 2 copper does not present visible absorbance, while the type 3 coppers have an absorption maximum at 330 nm (Mester and Tien, 2000;ten Have and Teunissen, 2001). It was demonstrated that, in the presence of suitable mediators, laccase is capable to oxidize a considerably larger range of compounds, such as PAHs (Peng et al, 2015).…”
Section: Characteristics Of Laccasementioning
confidence: 99%
See 2 more Smart Citations
“…The type 2 copper does not present visible absorbance, while the type 3 coppers have an absorption maximum at 330 nm (Mester and Tien, 2000;ten Have and Teunissen, 2001). It was demonstrated that, in the presence of suitable mediators, laccase is capable to oxidize a considerably larger range of compounds, such as PAHs (Peng et al, 2015).…”
Section: Characteristics Of Laccasementioning
confidence: 99%
“…xenobiotic and phenolic lignin model compounds Peng et al, 2015). Earlier, its application was limited because of the low oxidation potential, thus, in the presence of an appropriate mediator; laccases show higher oxidation capability resulting in numerous biotechnological applications involving oxidation of non-phenolic lignin compounds and detoxification of various environmental pollutants (Upadhyay et al, 2016;Khambhaty et al, 2015).…”
Section: Mediators Of Laccasementioning
confidence: 99%
See 1 more Smart Citation
“…strain S133 in malt extract agar (Hadibarata and Kristanti 2012a, b). Likewise, Lac produced by Aureobasidium pullulans could degrade 20% of pyrene present in the culture medium (Peng et al 2015), and Lac activity of Pseudotramete gibbosa could reach 2841 U L −1 when cultivated under optimal conditions, with corresponding degradation efficiencies reaching 24.3% for pyrene (Chen 2008). Moreover, several publications have demonstrated that white-rot fungus produces Lac when cultivated in the presence of PAHs and have pointed out the importance of this enzyme in degradation of PAHs.…”
Section: Resultsmentioning
confidence: 99%
“…The amount of secretory laccases in R. mackenziei is consistent with what was recently described for black yeasts of the genus Fonsecaea ( Moreno et al 2017 ). Laccases may catalyze the oxidation of phenolic compounds and aromatic amines ( Peng et al 2015 ). The most abundant secreted peptidases belong to the S10 family, according to MEROPS (a proteolytic enzyme database), which contains a variable set of carboxypeptidases.…”
Section: Discussionmentioning
confidence: 99%